UDP-GLC:GLYCOPROTEIN GLUCOSYLTRANSFERASE-GLUCOSIDASE II, THE YING-YANG OF THE ER QUALITY CONTROL - D’Alessio, Cecilia (2010)
The N-glycan-dependent quality control of glycoprotein folding prevents endoplasmic to Golgi exit of folding intermediates, irreparably misfolded glycoproteins and incompletely assembled multimeric complexes. It also enhances folding efficiency by preventing aggregation and facilitating formation of proper disulfide bonds. The control mechanism essentially involves four components, resident lectin-chaperones that recognize monoglucosylated polymannose glycans, a lectin-associated oxidoreductase acting on monoglucosylated glycoproteins, a glucosyltransferase that creates monoglucosytlated epitopes in protein-linked glycans and a glucosidase that removes the glucose units added by the glucosyltransferase. This last enzyme is the only mechanism component sensing glycoprotein conformations as it creates monoglucosylated glycans exclusively in not properly folded species or in not completely assembled complexes. The glucosidase is a dimeric heterodimer composed of a catalytic subunit and an additional one that is partially responsible for the ER localization of the enzyme and for the enhancement of the deglucosylation rate as its mannose 6-phosphate receptor homologous domain presents the substrate to the catalytic site. This review deals with our present knowledge on the glucosyltransferase and the glucosidase.